The effect of financial behavior and income on investment decisions during the covid 19 pandemic with financial literacy as an intervening variable - Rahman, Kristanti; Yulian, Tri Nurindahyanti (Faculty of Economics and Business Mulawarman University, 2022)
This study aims to analyze the effect of financial behavior and income on invesment decisions during the Covid 19 pandemic with financial literacy as an intervening variable. The population and sample in this study were the people of Cilacap Regency, and tehe number of respondents was 100 people. Methods of data collection using a questionnaire. The data analysis technique uses multiple regression and for testing the intervening variables using the Sobel est. The results of this study indicate that financial behavior affects financial literacy, income affects financial literacy, financial behavior affects investment decisions, income affects investment decisions, financial literacy affects investment decisions, financial literacy mediates the relationship between financial behavior on investment decisions, and financial literacy mediates the relationship between financial behavior and decisions